Effect of Intestinal Levodopa-Carbidopa Infusion on Pharyngeal Dysphagia: Results from a Retrospective Pilot Study in Patients with Parkinson’s Disease - Bendix Labeit; Inga Claus; Paul Muhle; Sonja Suntrup-Krueger; Rainer Dziewas; Tobias Warnecke (Parkinson's Disease)
Background. Pharyngeal dysphagia is a common symptom of Parkinson’s disease (PD) leading to severe complications. PD-related pharyngeal dysphagia (PDrPD) may significantly improve in up to half of patients following acute oral levodopa challenge. Objective. The aim of this study was to investigate the effects of levodopa-carbidopa intestinal gel (LCIG) on PDrPD. Methods. Forty-five PD patients under LCIG treatment were available for retrospective analysis. In all patients with PDrPD who underwent flexible endoscopic evaluation of swallowing (FEES) in the clinical “on-state” both before and after implementation of LCIG treatment, FEES videos were systematically reassessed. PDrPD was characterized using a PD-specific FEES score evaluating premature bolus spillage, penetration/aspiration, and pharyngeal residue. Further, the duration of white-out was assessed, as a parameter for pharyngeal bradykinesia. Results. Eleven patients with PDrPD (mean age 74.6 ± 4.4 years; mean Hoehn and Yahr stage 3.8 ± 0.6) received FEES both before and after the onset of LCIG treatment. The mean swallowing score improved from 14.9 ± 7.3 to 13.0 ± 6.9 after implementation of LCIG; however, this difference was not significant (p=0.312). Premature bolus spillage decreased significantly (p=0.002) from 5.4 ± 1.1 to 3.6 ± 1.0, and white-out duration decreased significantly (p=0.002) from 984 ± 228 ms to 699 ± 131 ms after implementation of LCIG. Conclusions. LCIG may affect PDrPD and reduce premature bolus spillage and pharyngeal bradykinesia. Future studies with larger sample sizes are required to follow-up on these pilot results and identify which factors predict a good response of PDrPD to LCIG treatment.